PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBASIS LIVEWORKSHEETS TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS 10 FASE E DI SMA NEGERI 7 PADANG - Wella Armawati; Bigharta Bekti Susetyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Critical thinking is an important skill in learning Geography that requires analysis of spatial and regional phenomena. However, many students have difficulty in developing these skills due to learning methods that do not involve them actively. This study aims to analyze the effect of Discovery Learning model based on Liveworksheets on critical thinking skills of students in class 10 phase E at SMA Negeri 7 Padang. This study used a quantitative approach with pre-experiment method and One-Group Pretest-Posttest Design. The research sample was all students of class 10 Phase E 3 which amounted to 36 people, with saturated sampling technique. The research instrument was 10 essay questions based on Ennis' critical thinking indicators. The results showed an increase in the average score from the pretest of 13.28 to 24.67 on the posttest, with a difference of 11.39 points. The paired sample t-test showed significance <0.001, and the effect size value of Cohen's d was 2.841 which was classified as very high. The N-Gain of 0.4268 showed a moderate increase. Thus, the Discovery Learning model based on Liveworksheets proved effective in significantly improving students' critical thinking skills.